ESTE SUFICIENTĂ CLARITATEA? CÂTEVA CONSIDERAȚII DESPRE RECEPTAREA PROPOZIȚIEI 4.112 DIN TRACTATUS (Romanian Journal of Analytic Philosophy, 2024)
In sentence 4.112 of the Tractatus, Wittgenstein defines philosophy as an activity of logical clarification of thoughts. My aim in this study is a limited historical one, namely, to present the most significant reactions of Wittgenstein’s contemporary philosophers to this statement. I believe that the main attitudes were expressed by Russell in his lectures on logical atomism, by Ramsey in his review of the Tractatus, by Schlick in two studies in which he enthusiastically adhered to the conception proposed by Wittgenstein, and by Price at a conference entitled "Clarity is not Enough?"